2012
DOI: 10.1039/c2cc36273b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic core–hydrophilic shell-structured catalysts: a general strategy for improving the reaction rate in water

Abstract: A novel solid catalyst featuring a hydrophobic core-hydrophilic shell structure was synthesized for aqueous-phase reactions, which showed significant reaction rate enhancement effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
1
21
1
Order By: Relevance
“…Yang et al. demonstrated that the micelle‐like Pd/SiO 2 catalyst with a hydrophobic core and a hydrophilic shell functions as a micelle in the hydrogenation reaction, which drives the solubilisation of organic reactants in the water phase to alleviate the kinetic barriers caused by the transport of organic substrates to catalytic sites 11a. Herein, to demonstrate the miceller acceleration of the catalyst at the water–oil interface in Pickering emulsions, the CA of benzyl alcohol was measured on the catalyst surface.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al. demonstrated that the micelle‐like Pd/SiO 2 catalyst with a hydrophobic core and a hydrophilic shell functions as a micelle in the hydrogenation reaction, which drives the solubilisation of organic reactants in the water phase to alleviate the kinetic barriers caused by the transport of organic substrates to catalytic sites 11a. Herein, to demonstrate the miceller acceleration of the catalyst at the water–oil interface in Pickering emulsions, the CA of benzyl alcohol was measured on the catalyst surface.…”
Section: Resultsmentioning
confidence: 99%
“…The table contains information on the metal surface and RO activity for furans, as revealed by DFT analysis reported in refs. .…”
Section: Deoxygenation Of High‐carbon Oxygenatesmentioning
confidence: 97%
“…This strategy can be further enhanced by the design and application of hydrophobic catalysts with unique structural features. Catalysts with hydrophobic cores and hydrophilic shells, with Pd or other noble‐metal NPs loaded on the exterior surface, with radically arrayed pores, are suitable candidates to enhance the rate of hydrogenolysis of long‐carbon‐chain furan derivatives from fully hydrogenated oxygenates . This strategy of using a catalyst with a highly hydrophilic exterior support may offer a very high selectivity for the formation of the hydrogenolysis product resulting from selective RO.…”
Section: Deoxygenation Of High‐carbon Oxygenatesmentioning
confidence: 98%
“…[90][91][92][93] The hydrophobization of mesoporous materials via replacing surface hydrophilic Si-OH, with hydrophobic functionalities is of mesoporous materials can significantly improve hydrothermal stability, [94][95][96] adsorption efficiency toward organic molecules, [97][98][99][100][101][102][103] and catalytic reaction rate. [104][105][106][107][108][109][110][111] In this paper, we investigated adsorption graphene on MCM41 at distance 1.8 Å, 2 Å and 2.3 Å. Here, the adsorption energy is defined as …”
Section: Introductionmentioning
confidence: 99%